Renewable energy, landfill gas and EfW: now, next and future - Adu-Gyamfi, Kofi Apea (Cranfield University, 2009)
The United Kingdom (UK) has traditionally used landfill disposal as the predominant method of waste management. However, landfilling is unsustainable due to its harmful effects on the environment and public health. Under the European Union (EU) Landfill Directive (LFD), member nations are now required to divert biodegradable municipal waste (BMW) from landfills. At the same time, the UK has committed to the EU Renewable Energy Directive, which binds it to sourcing at least 15% of its energy mix from renewables by 2020. To meet these targets, the UK has to support alternative waste management options whilst achieving a considerable deployment of renewable energy technologies. The uptake of renewables displaces the use of fossil fuels and is important for climate change mitigation and future energy security. This research reviews the development of landfill gas utilisation and energy from waste (EfW) technologies as renewable energy sources in UK. The drivers, barriers and future trends of these technologies are also considered. The main findings of this study are that the most cost-beneficial EfW applications for the UK are: 1) Biomethane use as road transport fuel and 2) Small-scale EfW deployment at community level. These two options are easily implemented able and would result in substantial savings in carbon-dioxide (CO2) emissions. Land fill gas (LFG) utilisation is currently the most important source of UK renewable energy but outputs of LFG would decline due to impact of the LFD. It is therefore crucial that the UK develops the capacity of other renewables. This study concludes that EfW technologies can contribute up to 50% of UK renewables target by 2020. However, actual results would depend on the pace of investment in EfW projects and the availability of suitable feedstock.
Keywords: landfill disposal; landfilling; biodegradable municipal waste; renewables; EU Renewable Energy Directive; waste management